Improving Digital Booking Skills Accurately For Students Of Smk Negeri 1 Garut - Ratih Pratiwi; Uding Sastrawan; Agus Cahyana; Aldi Adi Pratama (Community Development Journal, 2022)
Economic growth in various sectors including the sub-sector of industry, trade and the development of information technology, robotics, computerization and other automation has encouraged the transfiguration of information technology in the accounting world, making the education system in the world of education move quickly and efficiently. This chain then has an impact on vocational learning in Indonesia. Students in the era of society 5.0 must qualified friendly with technology related to accounting in the industrial revolution era 4.0 is like software or accounting robots and big data. Based on initial observations, it was found that 100% of class XI students at SMK Negeri 1 Garut had never operated Android-based digital bookkeeping. To promote the applied profession of society 5.0 , it is necessary to conduct training on android-based accounting applications. The purpose of this service is to increase understanding in recording, presenting, and reporting financial statements that are faster, more precise, and accurate in order to equip students to enter the world of work. The method of activity consists of the stages of preparation, initial observation, program implementation with lectures and practical simulations directly on students using accounting software Accurate Lite. Simulation of bookkeeping practices in trading businesses is carried out by creating a business database, recording purchase and sales transactions, accounts payable and receivables, recording expenses, inventory and bank history and presenting reports. The results obtained are 89% of students are able to operate the bookkeeping system using Accurate Lite and present financial reports according to the provisions.